Determination of Optimum Insulation Thickness for Different Insulation Applications Considering Condensation - Kaynakli, Omer; Bademlioğlu, Ali Hüsnü; Ufat, Hande Tufekci (Univ Osijek, Tech Fac, 2018)
In this study, thermal insulation thickness used in the outer walls of buildings composing of different insulation applications having the same thermal resistance was optimized by considering condensation. The minimum insulation thickness required to prevent condensation (i.e. optimum insulation thickness) in building structural component was determined. Heat and mass transfer calculations within the structural component were performed with respect to various indoor-outdoor temperature and relative humidity values and results were given in graphs. It was observed that optimum insulation thickness is generally increased with an increase in the indoor temperature, indoor relative humidity and outdoor relative humidity. It was concluded that type of insulation application does not significantly affect optimum insulation thickness at low and medium level (Theta<0.60) indoor relative humidity conditions. It was also observed that externally insulated wall application generally yields better results at high indoor and outdoor relative humidity conditions.
Keywords: building outer wall; condensation; optimization; thermal insulation